Developing hi-tech agriculture in Vietnam - Nguyen, Thi Kim Anh (ĐHQG, 2016)
Nowadays, following the globalization tendency and technology explosion, hi-tech agriculture is a key element which determines the farmer's life and income. Besides, it helps strengthening competitive power of agricultural product in the international market. The objective of researching team is bringing out the meaning and role of hi-tech agriculture in socioeconomic development. Then, evaluating the reality of hi-tech agriculture development in Vietnam. From that points, researching team will propose some motions for improving manufacture and consume rate